(untitled) (Circe de clásicos y modernos, 2023)
Two passages in Curtius Rufus’ Historiae can be read within the context of a tradition in Roman historiography of including speeches by foreign enemies to voice critical views of Roman imperialism. In this paper, Darius’ pre-battle speech at Gaugamela (4.14.9-26) and the Scythian ambassador’s speech before Alexander (7.8.12-30) will be analyzed to show that behind an apparent rebuke of Alexander the Great emerges a strong criticism of Rome’s imperial expansion.